-27=-2x-7

Simple and best practice solution for -27=-2x-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -27=-2x-7 equation:


Simplifying
-27 = -2x + -7

Reorder the terms:
-27 = -7 + -2x

Solving
-27 = -7 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
-27 + 2x = -7 + -2x + 2x

Combine like terms: -2x + 2x = 0
-27 + 2x = -7 + 0
-27 + 2x = -7

Add '27' to each side of the equation.
-27 + 27 + 2x = -7 + 27

Combine like terms: -27 + 27 = 0
0 + 2x = -7 + 27
2x = -7 + 27

Combine like terms: -7 + 27 = 20
2x = 20

Divide each side by '2'.
x = 10

Simplifying
x = 10

See similar equations:

| -p-4=-12 | | -9-6x=-21 | | 8(2n-1)=6(6n+3)+8 | | 3/-4 | | 5p-16=10 | | -7x-12=2x-(5x-8) | | (k-8)/(4+k)=-0.2 | | 7+n/8=n | | 0=a-49 | | ((-3j-(-4))/-6)-8=12 | | -3x+4-2x=7x | | -7-10=3f-10 | | -y/4=-10 | | 16x=0.5 | | -1(z+5)=-1 | | 50+7x-6=13x-4 | | 2x^5/2+5x^3/2=7x^1/2 | | 12=3b-5b | | -7f-10=3f-10 | | 7/1(4/1) | | 7/1(4/1) | | -1(2+5)=-14 | | 53y=2 | | 4n^2-2=14 | | -3n=7n+10 | | 22x+2y=-20 | | 5a+45a+23b+5=25a+3b+56 | | 4/3x=6 | | 15y+10=160+40y | | 96=-6x+5(-x-5) | | 2x(x+1)=7 | | 8p-1+p=10p-9 |

Equations solver categories